THERAPEUTIC POTENTIAL OF DUNALIELLA SALINA EXTRACT ON LIPID ACCUMULATION AND ADHESION MOLECULES IN HYPERGLYCEMIC RATS - FAROUK K. EL-BAZ; HANAN F. ALY; GAMILA H. ALI; SAYEDA M. ABDO; SAFAA A. SAAD (International Journal of Pharma and Bio Sciences, 2016)
The present study aims to investigate the antidiabetic effects of Dunaliella salina ethanolic extract. The antihyperlipidemic and anti-adhesion role of D. salina extract was evaluated comparing to glibenclamide antidiabetic drug. Lipid profile; total lipid (TL), total cholesterol (TC) and triglycerides (TG), adhesion molecules (ICAM-1 and VCAM-1) possessed a significant increase in STZ-induced diabetic rats model. D.salina ethanolic extract remediation of diabetic rats ameliorating TC, TG, ICAM-1 and VCAM-1 towered normal control levels. From histopathological point of view STZ-induced diabetic rats showed deteriorative modifications in the cardiac architecture. While, supplementation of diabetic rats with D. salina extract demonstrated an improvement in heart tissue. Hence, it could be deduced that, D. salina extract appeared therapeutic approaches in hyperglycemia dominance.